READER CODE: ANALYSIS THROUGH BIOMETRIC OBSERVATIONS (Scientific journal of the Fergana State University, 2026)
This article discusses the scientific foundations of the new approaches developing in literary studies: the experimental and cognitive direction of biometric analysis. The function of this technology in a work of art and the degree of change in the internal and external state of the hero in this process are analyzed on the basis of a table. It is proved that this trend can provide an opportunity to assess the interaction between the text and the reader on a scientific, empirical basis.